Strategi Pengembangan Koperasi Unit Desa (KUD) Berkat Telaga Kecamatan Telaga Kabupaten Gorontalo - Yanti Saleh; Siska Ismail (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2015)
The purpose of this study (1) to determine the internal and external factors that influence the development of KUD Berkat, (2) determine the development strategy of KUD Berkat. The collection of data is based on surveys and interviews. Analysis of the data used is the SWOT analysis. These results indicate that strategy is applied to the activities of KUD Berkat which is a strategy (SO): Utilizing the business units that are managed by looking at market opportunities for commodities produced cooperatives, improve the quality of service to members, (ST): increase the business unit is managed in order to reduce competition intensifies, (WO): improve guidance and training of government employees and cooperative management, hiring back employees in accordance with the competencies required cooperative, (WT): optimizing a computerized system in order efensiensi and effectiveness of operational activities KUD Berkat, improve internal cooperation in the operational management of the cooperative.